2016
DOI: 10.1016/j.copsyc.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Group Paradigm and its maximal impact in research on social categorization

Abstract: One of the most influential paradigms in research on intergroup relations is the Minimal Group Paradigm. Initially motivated by an interest in understanding the basic determinants of social discrimination, this paradigm investigates the impact of social categorization on intergroup relations in the absence of realistic conflicts of interests, and for social categories that are arbitrary and novel. Based on a short overview of the main features of the paradigm and its impact on social-psychological theories, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 37 publications
2
65
0
1
Order By: Relevance
“…In other words, participants showed ingroup biases even in experimentally-created and otherwise arbitrary groups (so-called "minimal groups"). Since then, other studies have replicated and extended their findings using various attitudinal and behavioral measures, including other group induction methods like random assignment and participant choice (e.g., Brewer & Silver, 1978;Perreault & Bourhis, 1999; for reviews, see Dunham, 2018;Otten, 2016). In line with the original Tajfel studies, participants have been shown to more positively evaluate their minimal ingroup members, allocate more resources to them, and hold stronger implicit biases towards them.…”
Section: Minimal But Meaningful Social Identitiesmentioning
confidence: 79%
“…In other words, participants showed ingroup biases even in experimentally-created and otherwise arbitrary groups (so-called "minimal groups"). Since then, other studies have replicated and extended their findings using various attitudinal and behavioral measures, including other group induction methods like random assignment and participant choice (e.g., Brewer & Silver, 1978;Perreault & Bourhis, 1999; for reviews, see Dunham, 2018;Otten, 2016). In line with the original Tajfel studies, participants have been shown to more positively evaluate their minimal ingroup members, allocate more resources to them, and hold stronger implicit biases towards them.…”
Section: Minimal But Meaningful Social Identitiesmentioning
confidence: 79%
“…Indeed, ingroup bias appears even absent conflict, competition, or indeed any information whatsoever about the specific characteristics of the groups involved. The redbanner example is the minimal groups paradigm [24,25] (MGP; Box 1). While it admits of many variants, in its simplest and clearest instantiation isolated individuals are randomly assigned to previously unfamiliar social groups based on arbitrary cues such as a group-denoting color or novel label.…”
Section: Mere Membership and Its Consequencesmentioning
confidence: 99%
“…While it admits of many variants, in its simplest and clearest instantiation isolated individuals are randomly assigned to previously unfamiliar social groups based on arbitrary cues such as a group-denoting color or novel label. This manipulation, a social coin flip, has profound consequences, producing a wide range of biases in favor of the ingroup [25]. While the MGP is widely known, its consequences are broader than generally recognized, making it paradoxically both familiar and underappreciated.…”
Section: Mere Membership and Its Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the social identity literature, the extent to which we feel similar to, like, or favor other in-group members is indicative of the extent to which our identification with that group has been incorporated into our self-concept ( Hogg, 1992 , 1993 ; Ellemers et al, 1999 ; Leach et al, 2008 ). The minimal group paradigm which facilitates the measurement of in-group favoritism and out-group discrimination is one way of measuring the extent to which group membership has been incorporated into the self-concept and therefore had an effect on social identity ( Otten, 2016 ).…”
Section: Introductionmentioning
confidence: 99%